Evaluative study of glycerol photocatalytic degradation over CuFe2O4 and La-CuFe2O4 photocatalysts - Tan, Sze Yee (2015)
Glycerol is produced as a side product (10 wt %) during biodiesel synthesis. If left untreated, it can potentially degrade the environment. Moreover, its purification is cost-prohibitive. This study therefore aims to investigate the physicochemical properties of copper ferrite, CuFe2O4 for the photocatalysis of glycerol. The CuFe2O4 was synthesized employing co-precipitation method, with and without lanthanum dopant (La) to enhance the catalytic properties of the photocatalyst. Characterization of the physiochemical properties was carried out using He displacement, N2 physisorption, Field Emission Scanning Electron Microscope (FESEM) and X-ray Diffraction (XRD). The characterization results revealed that the CuFe2O4 synthesized had a density of 2.4953 g/cm3 while La-CuFe2O4’s density was 3.4734 g/cm3. CuFe2O4 showed better catalyst characterization than La-CuFe2O4 by showing higher pore volume and surface area of 0.1683 cm3/g and 102.37 m2/g, respectively. XRD results proved the CuFe2O4 crystal to be face-centered cubic. The photocatalytic degradation of 0.5 v/v % glycerol under visible light irradiation (Xenon lamp with wavelength 400-700 nm) over copper ferrite (30 wt % Cu) and copper ferrite doped with lanthanum (40 wt % La) was carried out to determine the effectiveness of the catalyst. The amount of hydrogen peroxide (H2O2) added to create a Fenton system was varied to determine the effect of H2O2 in the effectiveness of photodegradation. In the preliminary assessment of photoactivity property of CuFe2O4, it was found that CuFe2O4 can effectively degrade methylene blue (an organic dye). Nevertheless, it exhibited insignificant photocatalytic effect on glycerol. Significantly, it can be shown that by adding a minimum of 0.5 mL H2O2 (photo-Fenton system), photocatalytic degradation of glycerol can take place, whilst up to 1.0 mL H2O2 was required for significant glycerol degradation over La-CuFe2O4. The rate and extent of glycerol degradation increased with the amount of H2O2. This study has therefore proved that CuFe2O4 can degrade glycerol under visible light source in a photo-Fenton reaction.